Pengaruh Foreign Direct Investment, Inflasi, Nilai Tukar Dan Trade Openness Terhadap Pertumbuhan Ekonomi Negara D-8 - Zara Nurul Arifa; Nurjannah Nurjannah; Asnidar A (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to determine the effect of Foreign Direct Investment, Inflation, Exchange rates, and Trade Openness on economic growth in D-8 countries. The data used in this study are secondary data obtained from the world bank. This study employs panel data regression analysis for the periode 2020-2024, using the fixed effect model as the selected model. The results show that, partially, Foreign direct investment has a negative and insignificant effect on economic growth, inflation has a negative and significant effect on economic growth, the exchange rate has a positive and insignificant effect on economic growth, and trade openness has a positive and significant effect on economic growth. Simultaneously, Foreign direct investment, inflation, exchange rates, and Trade openness have a significant effect on economic growth in D-8 countries.